Anomalous Variations in Ionosphere TEC Before the Earthquakes of 2021 in the Different Parts of the Globe - Yadav, Kunvar Shardaprasad; Vadnathani, Rakesh Bhikhabhai; Goswami , Keyurgiri Rajendragiri; Patel, Priyanka Mahesh (Trends in Sciences, 2023)
The present article shows the satellite-based TEC data analysis for 6 earthquakes (M ≥ 6.0) from specific parts of the earth that occurred in 2021 during the low solar radiation period. In search of pre-earthquake signatures in the ionosphere, the study of the data of GPS-based TEC before the earthquake is needed. L1 and L2 frequency delays have shown STEC and VTEC formulations for Ionosphere electron density measurements. The TEC data shows unusual behavior from 1 to 30 days before an earthquake. The primary goal of this article is to investigate and establish the correlation of lithosphere atmosphere coupling before earthquakes. Dst and F10.7 solar flux parameters have shown solar radiation. Additionally, TEC data also represented as heat maps to confirm their location at the epicenter. This research might help us understand how ionosphere properties respond to seismic activity in the earth’s crust. HIGHLIGHTS There is a growing interest in studying the seismo-ionospheric relationship today An analysis of ionospheric density changes prior to earthquake is presented in this paper We have observed anomaly in TEC [riot o seismic condition, while There were no changes in solar indices. The results of TEC enhancements led us to believe they were responsible for these high TECs GRAPHICAL ABSTRACT